Expression of B7‐H3 and TIM‐3 in gastric‐type endocervical adenocarcinoma: prevalence, association with PD‐L1 expression, and prognostic significance - Yao Sun; Xin Zhou; Elena Lucas; Lili Chen; Huijuan Zhang; Hao Chen; Feng Zhou (Wiley, 2024)
Abstract Gastric‐type endocervical adenocarcinoma (GEA) is the second most common subtype of endocervical adenocarcinoma and has a poor prognosis. Anti‐programmed death‐1 and anti‐programmed death‐ligand 1 (PD‐L1) inhibitors have emerged as a major treatment option for GEA; however, data on the expression of other immune checkpoints in GEA are limited. We analyzed the expression of T‐cell immunoglobulin and mucin‐domain containing‐3 (TIM‐3) and B7 homolog 3 protein (B7‐H3) in 58 GEA and investigated their prognostic significance as well as association with PD‐L1 expression and other known prognostic factors. Applying the tumor proportion score (TPS) with a cutoff of 1%, B7‐H3 and TIM‐3 were present in 48.3% and 17.2% of cases, respectively. Applying the combined positive score (CPS) with a cutoff of 1, TIM‐3 expression was present in 70.7% of cases. Moreover, the expression of three checkpoints (B7‐H3, TIM‐3, and PD‐L1) was incompletely overlapping. Patients with B7‐H3 positive tumors (by TPS) or TIM‐3 positive tumors (by TPS) had significantly worse recurrence‐free survival (RFS) and overall survival (OS) (log‐rank). Using CPS, patients with TIM‐3 positive tumors showed significantly worse RFS (log‐rank). Similarly, B7‐H3 positivity (by TPS) and TIM‐3 positivity (by TPS) were associated with worse RFS and OS in univariate analysis. TIM‐3 positivity (by CPS) was associated with worse RFS in univariate analysis and the final Cox multivariate analysis. In conclusion, our results show that (1) B7‐H3 and TIM‐3 are frequently expressed in GEA and their expression overlaps incompletely with PD‐L1; and (2) both B7‐H3 and TIM‐3 are independent negative prognostic markers in GEA.